Tensile Strength and Macro-microstructures of A6061 CDFW Weld Joint Influenced by Pressure and Holding Time in the Upset Stage - Abdulla, Farg Abdulla M; Irawan, Yudy Surya; Darmadi, Djarot Bangun (Jurnal Rekayasa Mesin, 2018)
This paper aims to analyze the effect of pressure and holding time in the upset stage on tensile strength and macro-microstructures of continuous drive friction welded (CDFW) joints of aluminum alloys A6061. Friction weld specimens were welded using variations of upset pressure (40, 80, 120 MPa). The upset holding time was varied from 3, 10, to 20 seconds. Tensile strength test was conducted based on the AWS standard. The result showed that the higher upset pressure and the longer holding time in the upset stage are able to reduce the porosity of the CDFW weld joint and cause a higher tensile strength of the specimens. Meanwhile, from macro-mic restructures observation results, it was found that the specimen with maximum tensile strength has a wider partly deformed area (ZPD) and finer grains in the center of the specimen longitudinal section compared to those of the specimens with minimum tensile strength. It was occurred due to plastic deformation as the result of the higher pressure and the longer holding time in the upset stage. Fracture surface observation results indicate that in the specimen with a higher upset pressure and a longer holding time, has inflated fracture surface and the fracture zone exists in the heat affected zone, not in the interface like that of the specimen with lower tensile strength due to the lower upset pressure and the shorter holding time.